THE CONCEPT OF VERTICAL SANCTITY IN ENVIRONMENTALLY FRIENDLY STORE BUILDING DESIGN - I Made Sastra Wibawa; Shinta Enggar Maharani (Unmas Press, 2022)
The increasing population demands the provision of increased residential infrastructure as well. As a result of development in a horizontal direction, it causes land-use change. The concept of vertical development is rejected by some people because they feel cemer/leteh when they enter the lower floors, therefore an understanding of vertical sanctity is needed in the design of high-rise buildings. This study aims to reveal the relationship between vertical sanctity and high-rise building design, and public acceptance of high-rise building designs in an effort to realize environmentally-friendly residential infrastructure. The method used is interviews with stakeholders and input data from questionnaires so that it is known the relationship between vertical sanctity and high-rise building design. The results obtained are that there is a relationship between vertical sanctity and high-rise building design and that people accept a minimum vertical distance of sanctity that is applied in the design of high-rise buildings. It is hoped that this vertical sanctity concept can be worldwide and accepted by the international community.